Pengaruh Model Pembelajaran Scaffolding berbantuan Multimedia Interaktif terhadap Hasil Belajar Matematika dengan Mengontrol Gaya Berpikir Siswa SMP Negeri 2 Mengwi - Ni Luh Gede Yuliani; I Wayan Widana (FPMIPA IKIP PGRI Bali, 2018)
As for the purpose of this research is to know the difference of the results learn math between the students who join learning model scaffolding assisted multimedia interactive with students who join conventional after learning model controlled style think. Research is both his experiments ( experiment quasi research the real conditions ) and used design non equivalen control only group design . Population in this research is a whole class viii public junior high schools 2 mengwi as many as 10 classes which consisted of 367 people with involving samples from 2 72 class students taken with using a technique random sampling. Research instruments used for collecting data is the test results learning and instrument of chief style think. The data collected were analyzed using statistic descriptive and inferential. The testing of hypotheses use t-test and analysis kovarian ( anakova ). The results of the analysis to the first hypothesis, there is a difference model of learning and interactive multimedia-assisted scaffolding model results against the conventional learning learning math students. The results of the analysis to the second hypothesis by anakova showed no difference in the results of the study of mathematics among students who follow the scaffolding learning with interactive multimedia-aided students who follow the conventional learning model After controlled style of thinking. The results of these studies provide indications that the scaffolding Learning Model-assisted Interactive Multimedia can enhance the results of learning math with or without control of the thinking styles of the students.